Prevalência e fatores de risco para Trichomonas vaginalis em mulheres atendidas em unidades de saúde pública no município de Uberlândia-MG e comparação entre técnicas de diagnóstico - Grama, Daliane Faria (2011)
Trichomonas vaginalis is the causative agent of trichomoniasis, being transmitted sexually or through contaminated fomites. This study was conducted to determine the prevalence of the parasite, identifying possible risk factors associated with infection in the city of Uberlandia, Minas Gerais state, Brazil. Samples of vaginal secretions of 742 women from 15 public health centers were collected and epidemiological questionnaire was applied in order to meet socioeconomic and behavioral habits. Two distinct samples of each patient were collected and evaluated by culture and wet mount test. Moreover, pap smears done in the routine, was also collected, which is analyzed by a laboratory accredited by the city. The prevalence of T. vaginalis was 2.56%. Married women with eight or fewer years of education and with income equal to or less than three minimum wages were most prevalent infection by T. vaginalis, although not associated with infection. Risk factors associated with trichomoniasis were black ethnicity (p = 0.004), smoking (p = 0.03) and clinical signs (p = 0.005). Knowledge about sexually transmitted diseases was considered a protective factor (p = 0.006). Comparing the diagnostic methods, the culture was considered the gold standard for other diagnostic tests. The wet mount test had a sensitivity of 78.95% and specificity of 100%. The positive predictive value was 100% and negative predictive value was 99.45%. Of the total number of infected women diagnosed by culture method (n = 19), the wet mount test detected 15 positive women. The diagnostic method pap smear had a sensitivity of 26.32% and specificity of 100%. The positive predictive value was 100% and negative predictive value was 98.1%. Of the total number of infected women (n = 19), pap smear detected five positive. These factors contribute as important information in the socioepidemiologic study involving the parasite and are fundamental to control the disease and, although not compulsory notification in the departments of health of Brazil, greater efforts are needed to reduce the prevalence.